Design of C-TYPE passive filter for arc furnaces - R. Klempka (Metalurgija, 2017)
The article presents an example of power supply system modernization in one of Polish steelworks. For the existing power system containing 3rd harmonics filters it was necessary to design a C-type filter for the 2nd harmonics. Two design methods have been presented. The first method is based on the assumption concerning the desired harmonic current flow of filter adjustment between the filter and power grid. The second method was based on using a genetic algorithm, searching for the RT resistance value of the filter. Applying the genetic algorithm makes it possible to take into account the broad spectrum of the electrical environment where the filter will be working.